Factor Structure Analysis of Perceived Stress Scale Among Healthcare Students - Giordanne Guimarães Freitas; Marcos Pascoal Pattussi; Tonantzin Ribeiro Gonçalves (Liberabit)
Background: Although the Perceived Stress Scale (PSS-10) is widelyused, rigorous assessment of its internal structure among healthcarestudents remains necessary. Objective: To evaluate the psychometricproperties of the PSS in healthcare university students. Method:Two random samples totaling 399 healthcare students completedthe PSS-10. Exploratory factor analysis used WLSMV estimator withoblique rotation. Confirmatory factor analysis employed StructuralEquation Modeling with covariance matrix. Orthogonal bifactoranalysis tested PSS-10 dimensionality. Analyses were conducted forboth total sample and gender-stratified subgroups. Multi-groupconfirmatory factor analysis assessed gender equivalence of factorstructure. Results: Scale items showed satisfactory factor loadings(> .40), good internal consistency (α > .80) and reliability(ω > .84), and acceptable discriminant validity between factors(< .85). Correlations between PSS-10 factors and psychologicaldistress and resilience were of expected magnitude and direction.Confirmatory factor analysis indicated better adjustment parameters(RMSEA = .091; CFI = .977; SRMR = .032) for the two-factorsolution (negative perception and stress coping) for both the totalsample and sex. Conclusions: The two-factor model showed nomeasurement invariance across gender groups. Orthogonal bifactormodels supported PSS-10 unidimensionality. Despite statisticalnuances across factor models, the PSS-10 provides a robust, simple,unidimensional measure of perceived stress among healthcarestudents.